Parallel-Batch Scheduling With Deterioration and Group Technology - Cuixia Miao (IEEE Access, 2019)
Parallel-batch scheduling with deterioration and group technology is a modern scheduling model, in which the jobs are classified into groups by the similar production requirements, and setup time, which may be fixed or deterioration function of the starting time, is required between jobs of different groups. We consider this scheduling to minimize the makespan in this paper. Based on Fully Batching Longest Deteriorating Rate, we show that our two single-machine scheduling problems are solved in polynomial time. Procedure Partition (A, F, ρ) is useful for designing algorithm in combinational optimization. We use this procedure to present fully polynomial time approximation schemes for our two parallel-machine scheduling problems, which is the best algorithm as its' objective value can be fully close to the optimal value.